Development of a Genotyping‐in‐Thousands by Sequencing (GT‐Seq) Panel for Identifying Individuals and Estimating Relatedness Among Alaska Black Bears (Ursus americanus) - Eleni L. Petrou; Colette D. Brandt; Timothy J. Spivey; Kristen M. Gruenthal; Cherie M. McKeeman; Sean D. Farley; David Battle; Cory Stantorf; Andrew M. Ramey (Ecology and Evolution)
ABSTRACT The management and conservation of large mammals, such as black bears (Ursus americanus), have long been informed by genetic estimates of population size and individual dispersal. Amplicon sequencing methods, also known as ‘genotyping‐in‐thousands‐by sequencing’ (GT‐seq), now enable the efficient and cost‐effective genotyping of hundreds of loci and individuals in the same sequencing run. Here, we develop a GT‐seq panel for individual identification and kinship inference in Alaska black bears. Using genomic data from restriction site‐associated DNA sequencing of hunter‐harvested bears from Southcentral Alaska (n = 85), we identified 170 microhaplotype and single nucleotide polymorphism (SNP) loci that were highly heterozygous in local populations. To enable sexing of individuals, we also included a previously published sex‐linked locus in the GT‐seq panel. We empirically validated the GT‐seq panel using samples collected at different spatial scales. These samples included tissues (n = 82) obtained from bears within a small geographic area in Anchorage, Alaska, which were likely to be relatives as well as the hunter‐harvested samples collected from geographically widespread locations throughout Southcentral Alaska. Empirical validation indicated high genotyping success and genotype reproducibility across replicate subsamples. Computer simulations demonstrated that the GT‐seq panel had ample statistical power for distinguishing distinct individuals and first‐order relatives (parent‐offspring and full‐sibling pairs) from unrelated individuals. As a final proof of concept, the panel was used to identify individual bears and close kin sampled from urban and wild habitats in Anchorage, Alaska. We anticipate that the GT‐seq panel will be a useful genomic resource for the monitoring and management of Alaska black bear populations.